Comparing Factors Associated With Intimate Partner Violence Among Rural and Urban Women in Northern Uganda - Richmond, Robyn Lesley (Journal of interpersonal violence, 2023)
Intimate partner violence (IPV) is an important public health issue with negative effects at individual and societal levels. In northern Uganda, IPV prevalence is high but literature on it is limited. Northern Uganda has a long history of socio-economic and political upheavals, which are recognized risk factors for IPV. We compare IPV prevalence among rural and urban women in northern Uganda. This was a cross-sectional survey of 856 northern Ugandan women, 409 women living in rural areas, and 447 women working in an urban marketplace. Data were analyzed using logistic regression. High rates of emotional, physical, and sexual IPV were found. Almost four of five participants had experienced at least one type of IPV during their lifetime, and approximately half of the participants had experienced IPV in the 12 months prior to the survey. Many women stated that IPV was justified in certain situations. Younger age was a significant determinant of IPV in both cohorts (adjusted odds ratio [aOR] 0.95, 95% confidence interval [CI] [0.93–0.97]). Determinants of IPV among the rural cohort included male partner’s alcohol abuse (aOR 2.22, CI [1.34–3.73]); having been in a physical fight with another man (aOR 1.90, 95% CI [1.12–3.23]); and controlling behaviors (aOR 1.21, CI [1.08–1.36]). Possible protective factors in the urban cohort included markers of economic empowerment such as being the decision maker on large household items (59.2% vs. 44.6%, p = .002) and having a mobile phone (20.4% vs. 12.4%, p = .024). Our study shows that IPV is a significant issue in northern Uganda. Economic empowerment is associated with lower rates of IPV in urban women, and interventions to reduce gender wealth inequality may reduce IPV prevalence. Further studies on enablers of IPV and the effect of conflict on IPV prevalence are needed to inform future interventions.